Bilateral Herpes Simplex Keratoconjungtivitis: A Case Report - Said, George Raden Mas; Mustaram, Arief Akhdestira (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2022)
Introduction: Herpes Simplex Virus (HSV) is one of the DNA viruses known to infect the human eye. Herpes simplex keratitis is, in general, a unilateral disease. In patients with weakened immune systems, simultaneous bilateral involvement is an uncommon event.Purpose: To report a case of bilateral herpes simplex keratoconjunctivitisCase Report: A 22-year-old man arrives with the primary complaint of redness in both eyes in the last four days. The patient complained of blurred vision, tearing, and foreign body sensations. Ophthalmology examination of both eyes revealed a visual acuity of 1.0 in the right eye and 0.8 in the left eye, a dendritic lesion, and decreased corneal sensation. The patient was diagnosed with bilateral keratoconjunctivitis HSV and was treated with acyclovir ointment, levofloxacin eye drops, acyclovir 400 mg five times daily, and vitamin C 500 mg.Discussion: Bilateral herpes simplex keratitis can occur in both immunocompromised and immunocompetent individuals. Recurrence of HSV infectious keratitis is common. Factors such as emotional stress, fever, postoperative tear dysfunction, ultraviolet (UV-A) radiation exposure, and ocular (accidental or surgical) trauma have also been related to the reactivation of the herpes simplex virus. History, physical, and laboratory examinations support the patient’s diagnosis to get the appropriate treatment.Conclusion: Due in part to the virus's increased virulence or changed host vulnerability, concurrently occurring bilateral herpetic keratitis has a high incidence of consequences. Delaying the advancement of corneal damage and lessening the intensity and frequency of viral assaults necessitates the timely administration of medicine upon diagnosis.